Gene silencing and applications for functional gene validation: the case of geminiviruses (2011)
Plants are able to recognize and degrade double-strand RNA molecules employing the mechanism of post-transcriptional gene silencing (PTGS). PTGS is both a vegetal defense strategy against viral infections and a conserved eukaryotic mechanism for regulate endogenous gene expression. The VIGS methodology(Virus Induced Gene Silencing) uses this mechanism to selectively silence genes employing viral vectors, which contain the target gene, becoming a tool for functional gene validation. Geminiviridae family, with the Begomovirus, Curtovirus, Mastrevirus and Topocuvirus genera, encompass viruses of circular, single-strand DNA packed in icosahedric geminated particles, and some of them had been evolved to infect particular plant species. Classification of these genera is based in the genome organization, the type of host plants and the insect vector that transmits the virus. Geminiviruses are able to induce gene silencing (GS) and therefore they have been used to develop VIGS–based methodologies for functional gene silencing. This review describes the molecular mechanism of gene silencing, with emphasis in gene silencing induced by Geminiviruses and the applications for a staple crop as cassava.